Deep Learning-Based Human Recognition Through the Wall using UWB radar - Pongpol Assawaroongsakul; Mawin Khumdee; Pattarapong Phasukkit; Nongluck Houngkamhang (My University, 2021)
Human activity detection in obscured or invisible area, for instance, human detection through the wall has become an interesting topic because it has potential for security, rescue, activity analysis application, etc. UWB radar, a detection system produces short radio frequency pulses and measures the reflected signals which UWB pulses have high spatial resolution and enable penetration in dielectric materials, was used to collect human activity through the wall signals at the frequency range of 3 GHz in this research. Subsequently, we applied signal data with the Deep Neural Network model to classify 5 classes of human activity including standing, walking, sitting, laying, and no-human gave the F1 score up to 96.94%.
Keywords: Non-Invasive Vital Sign Monitoring; Microwave Imaging and Scattering Analysis; Advanced SAR Imaging Techniques